2022
DOI: 10.3390/sym14112366
|View full text |Cite
|
Sign up to set email alerts
|

A New Symbolic Time Series Analysis Method Based on Time-to-Space Mapping, through a Symmetric Magnetic Field, Quantized by Prime Numbers

Abstract: This work presents a new analysis method for two-symbol symbolic time series based on the time-to-space mapping achieved through a device of current carrying circular rings. An algorithm based on the theory of prime numbers is proposed for the approximate estimation of the stratified magnetic field produced by the aforementioned device. The main property of the specific algorithm is that it quantizes the stratified magnetic field. If a two-symbol symbolic time series is used to determine the flow directions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…It is known that this model undergoes a second-order phase transition when the temperature drops below a critical value [10,16]. Thus, for a lattice of 20 3 nodes in three dimensions (3D Ising model), the critical (or pseudocritical for finite-size lattices) temperature has been found to be T c = 4.545 (J ij =1). Considering the sweep of the whole lattice as an algorithmic time unit, the possible values that spin can have in the model are ±1.…”
Section: The 3d Ising Model and Its Waiting Timesmentioning
confidence: 99%
See 4 more Smart Citations
“…It is known that this model undergoes a second-order phase transition when the temperature drops below a critical value [10,16]. Thus, for a lattice of 20 3 nodes in three dimensions (3D Ising model), the critical (or pseudocritical for finite-size lattices) temperature has been found to be T c = 4.545 (J ij =1). Considering the sweep of the whole lattice as an algorithmic time unit, the possible values that spin can have in the model are ±1.…”
Section: The 3d Ising Model and Its Waiting Timesmentioning
confidence: 99%
“…In a series of works [1,2], it has been shown that the use of a device with circular rings carrying electric currents of the same intensity but in a random flow direction results in a symmetrical stratified magnetic field, i.e., a magnetic field that presents a zonal structure around an axis of symmetry. Furthermore, using the most recently introduced primenumbers-based algorithm (PNA) to simulate the magnetic field of the specific device [3], the quantization of the above-mentioned stratified magnetic field is achieved, i.e., the magnetic field values' zones can be converted to quantized magnetic field values. Thus, if a two-symbol symbolic time series (using, for example, the symbols "+1", "−1") is employed to determine the flow directions of the rings' currents, a time-to-space mapping of the dynamics of the system producing the time series, is achieved [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations